Exploring Student’s Experiences in Learning English Using Digital Stories: A Narrative Research - Wulan Setia Wardah; Arilia Triyoga (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Digital storytelling merges traditional storytelling with digital media, creating short films that blend photos, text, video clips, animations, and music using computer-based tools. This narrative research study examines the experiences of students utilizing digital storytelling to enhance their English learning journey. Employing qualitative methods and narrative inquiry, the study conducted semi-structured interviews with a fourth-semester student from the English Letters Department of Universitas Ahmad Dahlan. The narrative inquiry ensured accurate and consistent data recording. The findings highlight the participant’s early exposure to English through songs and movies, which laid a foundational understanding of the language. The study reveals that digital storytelling is a multifaceted learning medium. The participant engaged with English content on platforms like the BBC website, significantly improving his language skills. Creating his own digital stories further honed his speaking, listening, vocabulary, and writing abilities. Crafting scripts for digital storytelling particularly advanced his creative storytelling skills. Moreover, the study sheds light on the participant’s challenges and successes with digital storytelling. One notable challenge was understanding native speakers’ speech, which differed from the non-native speaker's pronunciation typically taught in schools. However, the interactive nature of digital storytelling provided an engaging and effective way to enhance language skills, surpassing traditional learning methods.